2011
DOI: 10.1021/cn200089j
|View full text |Cite
|
Sign up to set email alerts
|

O-Hydroxyacetamide Carbamates as a Highly Potent and Selective Class of Endocannabinoid Hydrolase Inhibitors

Abstract: The two major endocannabinoid transmitters, anandamide (AEA) and 2-arachidonoylglycerol (2-AG), are degraded by distinct enzymes in the nervous system, fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL), respectively. FAAH and MAGL inhibitors cause elevations in brain AEA and 2-AG levels, respectively, and reduce pain, anxiety, and depression in rodents without causing the full spectrum of psychotropic behavioral effects observed with direct cannabinoid receptor-1 (CB1) agonists. These findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…FAAH and MAGL inhibition was evidenced by quantification of increases in AEA/OEA and 2-AG, respectively, in the medial prefrontal cortex, hippocampus, and caudate putamen of mouse brain. In general, the degree of selectivity of each drug for FAAH and MAGL, as reported previously (Fegley et al, 2005;Ahn et al, 2009;Long et al, 2009c;Niphakis et al, 2012), was confirmed under the current experimental conditions. Because changes in endocannabinoid content were not region dependent, these particular brain areas did not appear to differ in their potential contribution to the discriminative stimulus effects of Δ 9 -THC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…FAAH and MAGL inhibition was evidenced by quantification of increases in AEA/OEA and 2-AG, respectively, in the medial prefrontal cortex, hippocampus, and caudate putamen of mouse brain. In general, the degree of selectivity of each drug for FAAH and MAGL, as reported previously (Fegley et al, 2005;Ahn et al, 2009;Long et al, 2009c;Niphakis et al, 2012), was confirmed under the current experimental conditions. Because changes in endocannabinoid content were not region dependent, these particular brain areas did not appear to differ in their potential contribution to the discriminative stimulus effects of Δ 9 -THC.…”
Section: Discussionsupporting
confidence: 91%
“…SA-57 was synthesized in the laboratory of B.F.C. as previously described (Niphakis et al, 2012). Rimonabant base and URB597 were obtained from the National Institute on Drug Abuse Research Technology Branch.…”
mentioning
confidence: 99%
“…Dual FAAH/MAGL inhibition and using peripherally restricted inhibitors of FAAH and MAGL are also among the promising strategies (38,39,48). Moving to the inhibition of endocannabinoid cellular uptake, there are some potential therapeutic effects observed with the use of membrane transporter inhibitors in animal models (30,38,40).…”
Section: Modulation Of the Endocannabinoid Systemmentioning
confidence: 99%
“…Testing commenced following pretreatment times of 10 minutes for cocaine; 30 minutes for THC; and 120 minutes for PF-3845, JZL184, and SA-57. The selection of these pretreatment times was based on previous reports with enzyme inhibitors and preliminary studies with cocaine and THC (Ahn et al, 2009;Long et al, 2009b;Niphakis et al, 2012). To investigate the role of CB 1 and CB 2 receptors in the effects of each drug on ICSS, rimonabant or SR144528 was administered 15 minutes prior to each test compound in a separate set of experiments.…”
Section: Behavioral Proceduresmentioning
confidence: 99%
“…Toward this end, we examined the dose-response relationships of the FAAH inhibitor Ahn et al, 2009), the MAGL inhibitor JZL184 (4-[bis(1,3-benzodioxol-5-yl) hydroxymethyl]-1-piperidinecarboxylic acid 4-nitrophenyl ester; Long et al, 2009a), and the dual FAAH/MAGL inhibitor SA-57 (4-[2-(4-chlorophenyl)ethyl]-1-piperidinecarboxylic acid 2-(methylamino)-2-oxoethyl ester; Niphakis et al, 2012). SA-57 inhibits FAAH more potently than MAGL, resulting in elevated levels of AEA and other FAAH substrates at low doses, and increased 2-AG levels with higher doses (Niphakis et al, 2012). Cocaine was included as a comparison drug, because it is well established to increase ICSS (Fish et al, 2010;Straub et al, 2010).…”
Section: Introductionmentioning
confidence: 99%